Robust parametrical optimization of the digital control systems with unstructured parametrical perturbations - Абрамович, О.О.; Тунік, А.А. (Proceedings of National Aviation University (archive), 2004)
The paper is devoted to the method of the influence estimation of unstructured parametrical perturbations at the digital control systems. The solving of this task is using the theorem of Charitonov and the small gain theorem. Its efficiency is illustrated by the example of digital flight control of small UAV (Unmanned Aerial Vehicle).